Pilot interviews of job satisfaction with offshore catering employees - Abdul Majid, Mohd Aliff; Othman, Mohhidin; Mohamad, Siti Fatimah; Abdul Halim Lim, Sarina (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Previous research indicates that employee’s job satisfaction plays a significant role in organizational performance. In this paper, we draw upon qualitative inquiry alongside offshore catering employees; the overall goal was to explore their satisfaction with the job. Although there have been a significant number of studies, the field continues to experience diversity of understandings and ambiguity in this discourse. Shifting our focus from hypothetical job context where job satisfaction is commonly studied, we draw on the findings to gain insights into these differing understandings of offshore catering employees as they engaged in isolated workplace. The pilot interview was conducted as inducement for a dissertation in developing a job satisfaction instrument in a particular context. In this small-scale pilot study, we explore the job satisfaction experiences of Mark and Karl, two offshore catering employees. Data in the form of in-depth, semi-structured interviews identified 44 codes, indicating 10 dimensions of job satisfaction derived from the emerging themes. Evidently, the qualitative findings present important attributes of job satisfaction among offshore catering employees. Results of this study shed light on the need for future investigation to extend the scope of the study, bringing different cultures in order to enhance the findings on job satisfaction across a broader spectrum.